Psychiatric hospitalisations for people who are incarcerated, 2009–2019: An 11-year retrospective longitudinal study in France. (April 2022) - Fovet, Thomas; Chan-Chee, Christine; Baillet, Maëlle; Horn, Mathilde; Wathelet, Marielle; D'Hondt, Fabien; Thomas, Pierre; Amad, Ali; Lamer, Antoine
Summary: Background: Despite the poor mental health status of people who are incarcerated, few studies have examined the number of psychiatric hospitalisations in this population. Since 2010, France has progressively opened nine full-time inpatient psychiatric wards exclusively for people who are incarcerated, called "specially adapted hospital units" ( unités hospitalières spécialement aménagées, UHSAs, 440 beds). This study aimed to present the annual rates of psychiatric hospitalisations and primary psychiatric diagnoses among people who are incarcerated in France from 2009 to 2019. Methods: We used discharge reports from the French national hospital database to describe longitudinal retrospective administrative data of psychiatric hospitalisations for people in jail and prison between 2009 and 2019, the age, sex, and principal diagnoses of these patients, the proportion of voluntary versus involuntary care, and the interactions between UHSAs and other facilities. Findings: Between Jan 1, 2009, and Dec 31, 2019, 32, 228 (92.2% men, n  = 29, 721; 7.8% women, n  = 2 507) incarcerated people were hospitalised for psychiatric care (64, 481 stays). The main diagnoses were psychotic disorders (27.4%), personality disorders (23.2%), and stress-related disorders (20.2%). The annual number of incarcerated people hospitalised in psychiatric care increased from 3263 in 2009 to 4914 in 2019. The gradual increase in the activity of UHSAs (300 hospitalisations in 2010 versus 3252 in 2019) was not associated with a reduction in the rate of hospitalisation of incarcerated people in local psychiatric hospitals. Interpretation: The creation of psychiatric hospitals specifically dedicated to the prison population has not stopped the hospitalisation of people who are incarcerated at psychiatric hospitals. These findings suggest that access to psychiatric hospitalisation remains problematic for people who are incarcerated in France. Funding: There was no funding source for this study.